Fermented lingonberry juice's effects on active MMP‐8 (aMMP‐8), bleeding on probing (BOP), and visible plaque index (VPI) in dental implants-A clinical pilot mouthwash study - Hanna Lähteenmäki; Taina Tervahartiala; Ismo T. Räisänen; Pirjo Pärnänen; Timo Sorsa (Wiley, 2022)
Abstract Objectives We aimed to study the effects of fermented lingonberry juice (FLJ) as a mouthwash on the levels of active matrix metalloproteinase‐8 (aMMP‐8) in peri‐implant sulcular fluid (PISF), bleeding on probing (BOP), and visible plaque index (VPI). We hypothesized that FLJ rinsing could reduce inflammation (aMMP‐8 and BOP) and microbial load (VPI) in the oral cavity, especially around dental implants. Materials and Methods A clinical pilot study was performed using FLJ as a mouthwash. The inclusion criteria were at least one dental implant in the anterior or posterior areas with a screw‐retained crown. Ten participants used 10 ml of mouthwash twice a day for 15 days, and 10 participants served as the control group. Point‐of‐care tests (POCTs) were used to measure aMMP‐8 levels in the PISF, and BOP and VPI were recorded at the beginning of the trial and after 15 and 30 days. Results The FLJ mouthwash had a reductive effect on aMMP‐8, VPI, and BOP in the mouthwash group; however, there was no significant difference compared to the control group. The difference in VPI and BOP levels between the groups diminished after the lingonberry regimen ended. The decrease in aMMP‐8 levels appeared to continue even after discontinuation of the mouthwash regimen. Conclusion The reduction in the amount of plaque, aMMP‐8, and BOP by FLJ was promising and continuous considering the relatively short study period and sample size. FLJ is a natural and safe supplement for oral and dental implant home care. Further studies are required to verify these promising results.